Peningkatan Kualitas Pembelajaran di Kelompok Kerja Guru Gugus 1 Ngajum: Inovasi Whole-Brain Teaching - Agus Sholeh; Nara Sari; Siti Muntomimah; Shabina Qorina Fatiha; Nina Novitasari (Jurnal Pemberdayaan Masyarakat, 2024)
This community service program aims to enhance the quality of learning in KKG Gugus 1 Ngajum through the implementation of the Whole-Brain Teaching (WBT) innovation tailored to the needs of PAUD teachers. The activity began with a socialization session involving 30 out of 40 PAUD teachers in the region, focusing on introducing the concept of WBT as an interactive teaching approach that engages the whole brain of students. Following this, intensive training was conducted with hands-on methods, where teachers learned WBT techniques and developed lesson models that were relevant to local needs. Additionally, interactive learning technology was introduced to support the implementation of WBT in classrooms. Ongoing mentoring and periodic evaluations were carried out to ensure effective application of the method. The results of this program showed a significant improvement in student engagement and learning quality, with teachers successfully implementing WBT. Five WBT models developed during the training were compiled into a book that has been assigned an ISBN as an outcome of the community service. This program has made a positive contribution to improving teacher competencies and the quality of PAUD education, with the potential for broader application in other regions.